Effect of Drying with Far Infrared Dryer, Oven Vacuum, and Freeze Dryer on the Color, Total Carotene, Beta-Carotene, and Vitamin C of Spinach Leaves (Amaranthus Tricolor L.) - Asep Sopian; Ridwan Thahir; Tien R Muchtadi (Jurnal Teknologi dan Industri Pangan, 2005)
Spinach is a well known vegetable as a source of nutrition especially for is carotene. Soinach leaves need to be dried for application in product development of food like biscuit, extruded products and analysis. One the drying method that became popular is drying using infrared wave. The aim of this research was to compare the effect of blanching and drying (far infrared dryer, oven vacuum, and freeze dryer) on the color, total carotene, beta-carotene, and vitamin C of spinach leaves. Blanching and drying of increased brightness, a value, and b value. The a value is shows spinach brightness in mix red-green color while b value shows mix blue-yellow. Total carotene of fresh spinach decreased by 10.47% after blanching. Drying with vacuum decreased the total carotene by 39.31% (with blanching) and 31.66 (with blanching). Drying with freeze dryer decreased the beta carotene by 4.99% (with blanching) and 18.60% (with blanching). Drying with FIR dryer decreased spinach total carotene by 34.90% (with blanching) and 24.86% (with blanching). The beta-carotene of fresh spinach with balancing treatment decreased of by 16.53%.drying oven vacuum decreased the beta carotene by 42.80% (wiyh blanching) and 18.91% (with blanching). Drying with freeze dyer decreased the beta carotene by 29.03% (with blanching) the beta carotene. The decreased of beta-carotene is bigger than total carotene. Vitamin C of fresh spinach decreased by 20.35% after blanching. Drying with oven vacuum decreased of 55.77% (without blanching) and 65.42% (with blanching) f the vitamin C. drying with freeze dryer decreased the vitamin C by 13.21% (without blanching) and 30.67% (with blanching). Meanwhile, the vitamin C of spinach after drying with FIR dyer decreased of 60.53% (without blanching) and 70.29% (with blanching). Key words: Spinach, drying, blanching, far infra red dyer, oven vacuum, freeze dyer, total carotene, beta carotene, vit C.